Transmission Electron Microscopy - Williams, David B. (Springer, 1996)
How is this book any different from the many other books that deal with TEM? It has several unique features, but the most distinguishing one, we believe, is that it can really be described as a "textbook"-that is, one designed to be used primarily in the classroom rather than in the research laboratory. We have constructed the book as a series of relatively small chapters (with a few notable exceptions!). The contents of many chapters can be covered in a typical lecture of 50 to 75 minutes. The style is informal for easier reading; it resembles an oral lecture rather than the formal writing you would encounter when reading research papers. In our experience, the TEM books currently available fall into three major categories. They may be too theoretical for many materials science students; they attempt to cover all kinds of electron microscopy in one volume, which makes it difficult to include sufficient theory on any one technique; or they are limited in the TEM topics they cover. The rapid development of the TEM field has meant that many of the earlier books must automatically be placed in the third category. Although these books are often invaluable in teaching, we have not found them generally suitable as the course textbook in a senior-year undergraduate or first-year graduate course introducing TEM, so we have endeavored to fill this perceived gap.
A Textbook for Materials Science